Detection of calcitonin gene-related peptide based on increased antigen-driven interaction with antibody variable regions - Cheng, Yueqing; Gao, Yujie; Zhang, Shengshuo; Zou, Yujie; Zhao, Guangwei; Zheng, Liyuan; Hou, Binghui; Li, Mei; Dong, Jinhua (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Calcitonin gene-related peptide (CGRP) is involved in trigeminal neuralgia and migraine, and measuring the CGRP concentration in the serum is crucial for the early prediction of these conditions. Current methods for CGRP detection are primarily competitive enzyme-linked immunosorbent assays (ELISA), which have a narrow detection range. Methods: The genes of anti-CGRP antibody variable regions were cloned into pDong1 vector to obtain pDong1-CGRP/Fab, with which phage-Fab was prepared, and the concentration of CGRP was detected by competitive ELISA. The pDong1-CGRP/Fab was modified to obtain pDong1-CGRP/OS, with which the co-expression solution containing phage-displayed heavy chain variable fragments (phage-VH) and light chain was obtained. CGRP was detected by OS-ELISA based on phage-VH, antibody light chain, and anti-light chain antibody. The VL gene was cloned into the pMAL vector to obtain pMAL-VL(CGRP), with which maltose binding protein fused with VL (MBP-VL) was prepared. CGRP was detected by OS-ELISA employing MBP-VL and phage-VH. Results: OS-ELISAs that measure the CGRP concentration by quantifying the interaction between variable regions were investigated. OS-ELISA using phage-VH and secreted light chains in the same culture system exhibited a limit of detection (LOD) of 0.05 nM, offering higher sensitivity than competitive assay with an LOD of 2.07 nM, whereas using phage-VH and separately prepared MBP-VL exhibited an LOD of 0.15 nM and a broader detection range of 0.15-500 nM than competitive ELISA, whose detection range was 0.75-10 nM. Discussion: The combination of the two OS assays achieved high sensitivity and a broad detection range for CGRP, which may have significance in clinical applications.